Evaluating dynamic tire pressure variations on uneven road surfaces - huynh van, quan (Vietnam Journal of Science and Technology, 2025)
In order to accommodate Vietnamese conditions, this paper presents a road profile model that combines the international roughness index (IRI) with the Gaussian white noise (GWN) function. The proposed model deviated from the cosine model and the original model by about 3.6% and less than 0.1%, respectively. This model served as an excitation source for analyzing the dynamic interaction between vehicles and pavements. Employing the MATLAB-Simulink tool, numerical dynamic analyses of a quarter-car model (QCM) were conducted under various vehicle speeds and road surface conditions. When comparing dynamic and static conditions, the results indicated a difference of over 10% in the tire pressure applied to the pavement. For example, the deviations were 9.9, 16.4, 26.3, and 38.3% at 40 km/h with IRI values of 1.8, 3.0, 5.0, and 7.0.